Comparison between a New Optical Biometry Device and an Anterior Segment Optical Coherence Tomographer for Measuring Central Corneal Thickness and Anterior Chamber Depth. (14th June 2016) - Huang, Jinhai; Lu, Weicong; Savini, Giacomo; Chen, Hao; Wang, Chengfang; Yu, Xinxin; Bao, Fangjun; Wang, Qinmei
Abstract : Purpose. To compare between a new optical biometer (AL-Scan, Nidek Co., Aichi, Japan) and an anterior segment optical coherence tomographer (Visante AS-OCT, Carl Zeiss Meditec, Dublin, USA) for measuring central corneal thickness (CCT), anterior chamber depth (ACD), and aqueous depth (AD). Methods. Sixty-three eyes of 63 normal subjects were examined with AL-Scan and Visante AS-OCT in this prospective study. One eye per subject was measured three times with both devices to record their CCT, ACD, and AD. All procedures were performed by the same operator. Agreement between the two devices was assessed using paired t -tests, Bland-Altman plots, and 95% limits of agreement (LoA). Results. The mean CCT, ACD, and AD measured by AL-Scan were538.59 ± 27.37 μ m, 3.70 ± 0.30 mm, and3.16 ± 0.30 mm, respectively. The mean values obtained by the Visante OCT were536.14 ± 26.61 μ m for CCT, 3.71 ± 0.29 mm for ACD, and3.17 ± 0.29 mm for AD. The mean CCT by the AL-Scan was higher than that obtained by the Visante AS-OCT (difference =2.45 ± 6.07 μ m, P < 0.05 ). The differences in ACD and AD measurements were not statistically significant. The 95% LoA of CCT, ACD, and AD were between −9.44 and 14.35 μ m, −0.15 and 0.12 mm, and −0.15 and 0.12 mm, respectively. Conclusions. Since these two devices were comparable for measuring CCT, ACD, and AD, their results can be interchangeably used in the clinic.